PRINCIPLES OF DESIGNING MODERN ENTERTAINMENT FACILITIES NEAR HISTORICAL CULTURAL HERITAGE OBJECTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides a comprehensive analysis of the theoretical and practical foundations of designing modern entertainment venues near historical cultural heritage sites. The study examines the spatial, visual, functional and social relationships between entertainment infrastructure and the historical area based on international heritage protection standards - UNESCO's Historic Urban Landscape concept, ICOMOS charters on urban heritage preservation, and local legal and regulatory documents. The article scientifically presents the principles of the impact of new facilities on the scale and silhouette, landscape integration, improving the quality of public spaces, managing tourist flows, and introducing modern technologies in the historical environment. The practical significance of the study is that the developed principles serve to increase the cultural and economic potential of the construction of modern entertainment venues in historical areas without damaging the heritage layer.